Memutus Siklus JUDOL: Strategi Ajaran Buddha untuk Mengatasi Kecanduan Judi Online di Era Digital - Luwiha Luwiha; Viola Viola; Mega Julianti; Rina Manggalani; Troi Bao Tang (LPPM STIAB JINARAKKHITA LAMPUNG, 2026)
This study investigates the effects of meditation, social association, and self-control (sīla) on Online Gambling Addiction Reduction in the digital era, drawing upon principles from the Sigalovada Sutta and the Visuddhimagga. A structural equation modeling approach is employed to examine the relationships among these variables. The findings indicate that meditation has a significant positive effect on Online Gambling Addiction Reduction, as reflected by a high beta coefficient. Furthermore, self-control serves as a strong mediating variable in the relationship between meditation and the reduction of gambling addiction, while social association also contributes positively, albeit to a lesser extent. These results support key Buddhist teachings that emphasize moral discipline and the importance of supportive social environments in mitigating addictive behaviors. Notably, the findings suggest that internal mechanisms particularly self-awareness and emotional regulation developed through meditation play a more critical role in resisting gambling impulses than external influences alone. Overall, this study highlights meditation and self-control as central pillars in Online Gambling Addiction Reduction and offers important theoretical and practical implications for developing more effective intervention strategies in the context of behavioral addiction.